If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9p + 1)(9p + -1) = 0 Reorder the terms: (1 + 9p)(9p + -1) = 0 Reorder the terms: (1 + 9p)(-1 + 9p) = 0 Multiply (1 + 9p) * (-1 + 9p) (1(-1 + 9p) + 9p * (-1 + 9p)) = 0 ((-1 * 1 + 9p * 1) + 9p * (-1 + 9p)) = 0 ((-1 + 9p) + 9p * (-1 + 9p)) = 0 (-1 + 9p + (-1 * 9p + 9p * 9p)) = 0 (-1 + 9p + (-9p + 81p2)) = 0 Combine like terms: 9p + -9p = 0 (-1 + 0 + 81p2) = 0 (-1 + 81p2) = 0 Solving -1 + 81p2 = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 81p2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 81p2 = 0 + 1 81p2 = 0 + 1 Combine like terms: 0 + 1 = 1 81p2 = 1 Divide each side by '81'. p2 = 0.01234567901 Simplifying p2 = 0.01234567901 Take the square root of each side: p = {-0.111111111, 0.111111111}
| (x-9.6)(3x+0.9)= | | 9(x-2)=2(x+3) | | 4d+7=15 | | 8(7-p)-8=-16(p-2) | | (3w)(w)=(3w-2)(w-2)+36 | | X-3=(-3) | | 3x+6=2x-5 | | 3(n-5)=-2n | | 7x-9-2x=10-3x+5 | | 6(x-2)+3=3x-15 | | 6(x-2)+3=3z-15 | | 8a-10=3(6-2a) | | x+7x+15x=29x+18 | | 3(x-3)=5(x+3) | | 3(d-8)-5=9(d-12)+1 | | 15-3G=15 | | 2x+1-4x-9=12 | | 4(x-9)=3(2x-8) | | 3(x-1)=24 | | 13=6x-5 | | 4x+2=-22 | | 7x-14=4x+13 | | -2.9m+7=2.1m+3.5 | | 50-2x=44 | | 0.50y=-7 | | 0.50W=-2 | | 4(2w+1)=52 | | n-7=18+3 | | 7e^3x=2 | | -8+33.3y=2 | | A+6=14 | | -9+7b=8b-7 |